Costs and quality of life in community-dwelling patients with Alzheimer's disease in Spain: results from the GERAS II observational study. (19th July 2017) - Olazarán, Javier; Agüera-Ortiz, Luis; Argimón, Josep María; Reed, Catherine; Ciudad, Antonio; Andrade, Paula; Dilla, Tatiana
ABSTRACT: Background: Country-specific data on resource use and costs associated with Alzheimer's disease (AD) help inform governments about the increasing need for medical and financial support as the disease increases in prevalence. Methods: GERAS II, a prospective observational study, assessed resource use, costs, and health-related quality of life (HRQoL) among patients with AD and their caregivers in Spain. Community-dwelling patients aged ≥55 years with probable AD, and their primary caregivers, were recruited by study investigators during routine clinical practice and assessed as having mild, moderate, or moderately severe/severe (MS/S) AD dementia based on patient Mini-Mental State Examination scores. Costs of AD were calculated by applying costs to resource-use data obtained in caregiver interviews using the Resource Utilization in Dementia instrument. Total societal costs included patients' health and social care costs and caregiver informal care costs. Baseline results are presented. Results: Total mean monthly societal costs/patient (2013 values) were €1514 for mild ( n = 116), €2082 for moderate ( n = 118), and €2818 for MS/S AD dementia ( n = 146) (p value <0.001 between groups). Caregiver informal care costs comprised most of the total societal costs and differed significantly between groups (€1050, €1239, €1580, respectively; p value = 0.013), whereas patient healthcare costs did not. Across AD dementia severity groups, patient HRQoL (measured by proxy) decreased significantly (p value <0.001), caregiver subjective burden significantly increased (p value <0.001) and caregiver HRQoL was similar. Conclusions: Societal costs associated with AD in Spain were largely attributable to caregiver informal care costs and increased with increasing AD dementia severity.